Suitability of Mangrove Kayu Arang Village as a Mangrove Ecotourism Area in West Bangka Regency, Bangka Island - Umroh, Umroh; Akhrianti, Irma; Pamungkas, Aditya; Wahidin, La Ode; Utami, Eva; Pryambada, Agung; Hudatwi, Mu’alimah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Kayu Arang Village has high potential biological resources, such as Satang shrimp and Tirus Fish in the Kayu Arang river area. The wealth of biological resources in the Kayu Arang River is also supported by the existence of mangrove ecosystems that have high density and nature. The mangrove ecosystem really needs to be developed to improve the condition of Arang wood village. The development of mangrove ecosystems in Kayu Arang must first be calculated Tourism Suitability Index, so that the potential of mangroves for ecotourism can be known. This is because mangrove ecosystems have enormous potential and benefits, and contribute to increasing community income. Some stages of this research study include: sausagealization of mangrove ecotourism and providing understanding of mangrove potential, collecting mangrove data (density, mangrove species, growth), endemic biota both in sediments (macrobenthos), rivers (fish, shrimp, crabs) and aboreal (monkeys, birds). The next stage is to see the level of suitability of the mangrove area of Kayu Arang Village to become ecotourism. Therefore, this research study aims to determine the potential of mangrove ecosystems to be used as mangrove ecotourism areas in Kayu Arang Village, West Bangka. The results of the mangrove ecosystem suitability analysis show that the mangrove area in Kayu Arang Village can be used as an ecotourism area. With government support, it will be able to accelerate the realization of an ecotourism area in Kayu Arang Village, West Bangka. LoA, Plagiarism